PENGARUH KOMUNIKASI KELUARGA TERHADAP KARAKTER SANTUN REMAJA - Tagonna Serasi Asnita Simanjuntak; Muhammad Jais; Wila Sariarien (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: (1) determine the level of family communication in Pangkalan Kerinci Kota, Pelalawan Regency; (2) determine the level of adolescents’ polite character in Pangkalan Kerinci Kota, Pelalawan Regency; and (3) determine the effect of family communication on adolescents’ polite character in the area. This study employed a quantitative approach with an ex-post facto research design. The population of this study consisted of 1,115 adolescents aged 15–18 years in Pangkalan Kerinci Kota, Pelalawan Regency. The sampling technique used the Slovin formula with a 10% error rate, resulting in a sample of 92 respondents. Data collection techniques included questionnaires, observations, and documentation. Data analysis used descriptive statistics and inferential descriptive analysis with the assistance of SPSS version 26. The results showed that the level of family communication was in the high category with a mean score of 3.71, while adolescents’ polite character was also in the high category with a mean score of 3.70. Furthermore, there was a positive and significant effect of family communication on adolescents’ polite character with a significance value of 0.000 < 0.05. The contribution of family communication to adolescents’ polite character was 36.6% and was categorized as low because family communication is not the only factor influencing adolescents’ polite character.